The Influence of Asset Management on Optimizing the Utilization of Fixed Assets in Batu Bara Government - Sukma, Kirana Rahmalia; Siahaan, Elisabet; Talarosha, Basaria (Formosa Journal of Multidisciplinary Research, 2024)
Governance in Indonesia has experienced significant changes since the post-Reformation era of 1988, particularly with the implementation of Law Number 22 of 1999 on Regional Government, which initiated the decentralization of authority from the central to regional governments. This implementation was further reinforced by Law Number 32 of 2004, which emphasized the obligation of regional governments to manage their own affairs based on the principle of autonomy. This study examines the influence of asset management on the optimization of fixed assets in the Government of Batu Bara Regency. The population in this study consisted of 99 employees distributed across 35 work units, resulting in a sample of 79 respondents representing the population. The analysis method used was Partial Least Square (PLS), with questionnaires distributed to 79 respondents. The results showed that asset inventory did not have a significant influence on the optimization of fixed assets, whereas asset legal audit and asset valuation had a positive and significant influence. Asset supervision and control were found to moderate the influence of asset inventory on the optimization of fixed assets, but did not significantly moderate the influence of asset legal audit and asset valuation.